A pilot study testing the iOS UB‐CAM delirium app. - Kuzmik, Ashley; Hannan, John; Boltz, Marie; Shrestha, Priyanka; Husser, Erica K.; Fick, Donna M.; Marcantonio, Edward R. (Journal of the American Geriatrics Society, 2023)
The article discusses research which developed, validated and field tested an Ultra-brief Confusion Assessment Method (UB-CAM), a two-step delirium identification protocol, and an iOS-based UB-CAM app for the iPhone and iPad. The study conducted UB-CAM assessments of patients in the Family-centered Function-focused Care cluster randomized trial to screen for delirium. It recorded the amount of time it took the assessment on the UB-CAM app.